Trade and climate change : issues in perspective : final report and synthesis of discussions - Cosbey, Aaron (International Institute for Sustainable Development WinnipegCA, 2008)
Focuses on six thematic areas viz. liberalization of low-carbon goods; border carbon adjustment; embodied carbon in traded goods; intellectual property rights; clean energy investment; and, standards and labelling.